Perancangan Alat Pengukur Suhu Badan dan Kadar Oksigen Dalam Darah Menggunakan Mikrokontroler - Wahyusari, Retno; Wibowo, Lastoni; Amrozi, M Ali (Jurusan Informatika STTR Cepu, 2023)
The three symptoms of Corona that are most often experienced are general symptoms such as fever, cough and shortness of breath. Based on this, the government has made regulations to measure body temperature before entering a public space. Even though it's not really something that becomes the main determinant, we still need it for several public locations. In addition to body temperature, checking oxygen levels in the blood is also one of the important indications needed to see a person's body health. The condition is declared healthy if the body temperature is below 37o and oxygen levels are between 95-100. Devices for measuring body temperature and oxygen levels in the blood are tools that support the implementation of health protocols. Utilizers of the tool can detect early health problems based on body temperature and oxygen levels in the blood, especially the corona virus. The test results show that the tool has an accuracy rate above 90%, where the body temperature accuracy is 94.33% and the oxygen level accuracy is 98.63%. This shows that the tool can replace manufacturing tools, so this tool is suitable for use to help create a new normal era that pays attention to health protocols.